The Effectiveness of New Solar Photovoltaic System with Supercapacitor for Rural Areas - Romli, Muhammad Izuan Fahmi; Kumar Rajkumar, Rajprasad; Wan, Wong Yee; Lee Wai, Chong; Arelhi, Roselina; Isa, Dino (International Journal of Renewable Energy Development, 2016)
Countries like Malaysia have more that 70% of its population living in rural areas. Majority of these rural areas lie in regions where most villages do not have grid connected electricity. Renewable energy using photovoltaic (PV) panels offers an alternative and cost efficient solution that exploits the yearlong abundance of sunlight available in countries like Malaysia. The main problem with PV systems is the high maintenance costs in replacing batteries every few years which makes PV systems unattractive for rural areas. A full scale PV system, developed in Semenyih Malaysia, aims to increase battery lifetime and reduce maintenance costs by incorporating supercapacitors. The system was developed in a life-sized cabin to mimic a rural home. A programmable load is used to test the system with the load profile of a typical rural household usage. Experimental and simulation results show that the supercapacitor bank is able to reduce the stress on the battery by absorbing peak current surges. Results also show that the system is able to maintain a high battery state of charge during the entire day.Article History: Received June 17th 2016; Received in revised form August 16th 2016; Accepted Sept 10th 2016; Available onlineHow to Cite This Article: Fahmi, M.I., Rajkumar, R., Â Wong, Y.W., Chong, L.W., Arelhi, R., and Isa, D. (2016) The Effectiveness of New Solar Photovoltaic System with Supercapacitor for Rural Areas. Int. Journal of Renewable Energy Development, 5(3), 249-257.http://dx.doi.org/10.14710/ijred.5.3.249-257